AF397, AK652, AN193 and AV442 antibodies recognize a GFP-tagged protein by western blot - Marchetti, Anna (Antibody Reports, 2022)
AF397, AK652, AN193 and AV442 antibodies against the GFP protein recognize a GFP-tagged human TAC protein by western blot.